The Sharpen Role of Community Health Center and Clinic Accreditation Surveyors (Literature Review) - Ahyar Wahyudi; Friedrich Max Rumintjap; Siswanto Pabidang (PT FORMOSA CENDEKIA GLOBAL, 2023)
The quality of health services has long been a central topic in discussions regarding health system optimization. As a basis, Hippocrates, known as the